Therapeutic stroking on quality of sleep - Dr.ARUNA.S, PH.D; MRS.THENMOZHI, M.SC (N); MRS.KARPAGAM.K, M.SC (N); MR.BENIN SUNDAR.M.SC, (N); MS.SUZY LEWIS CHEN, M.SC(N) (International Journal of Pharma and Bio Sciences, 2016)
Sleep is a periodic state of physiological rest occurring at regular intervals in which the eyes usually close, the muscle relax and responsiveness to external events decreases, consciousness is suspended and metabolic rate is decreased. The patient admitted in the hospital with critically ill, especially in the Intensive care unit known to have a disturbed sleep. Though many receive medications to promote sleep, among the various non-pharmacological interventions, therapeutic stroking is a method of kneading massage is the best intervention to reduce fatigue and improve sleep. The aim of the study is to determine the effectiveness of therapeutic stroking on quality of sleep in myocardial Infarction patients. A research design adopted for this study was quasi-experimental design. The sample size was 30 in experimental group and 30 in control group. Sample was selected by using convenient sampling technique. Therapeutic stroking was given for 10 minutes at night for 5 days for experimental group and control group received regular intervention. Their quality of sleep was measured by Groningen Sleep Quality Score (GSQS) before as well as after the intervention in both groups. Data were analyzed by using descriptive and inferential statistics. Therapeutic stroking was found to be effective in improving the quality of sleep among patients with Myocardial Infarction at the level of P < 0.001. The study findings concluded that therapeutic stroking is the drug free choice of treatment in promoting the quality of sleep where as sleep quality deteriorated in the control group and 60% percent subjects had poor sleep without the intervention of therapeutic stroking. It is a simple non-pharmacological and cost effective method and can be used effectively for the improvement of the quality of sleep among patients with Myocardial Infarction.